36x-14=36x-6

Simple and best practice solution for 36x-14=36x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36x-14=36x-6 equation:


Simplifying
36x + -14 = 36x + -6

Reorder the terms:
-14 + 36x = 36x + -6

Reorder the terms:
-14 + 36x = -6 + 36x

Add '-36x' to each side of the equation.
-14 + 36x + -36x = -6 + 36x + -36x

Combine like terms: 36x + -36x = 0
-14 + 0 = -6 + 36x + -36x
-14 = -6 + 36x + -36x

Combine like terms: 36x + -36x = 0
-14 = -6 + 0
-14 = -6

Solving
-14 = -6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -22=11(2c-8) | | |-14|= | | (22-18)x(3+8)= | | x-24=6 | | 2(2)+3(4a)-4(3+3a)+3=0 | | 3y-24-6y+37= | | 4d^2-4d-80=0 | | x-8.8=-6.8 | | 2=2m+2+6m | | (q*q*q)-6(q*q)-21600=0 | | 12/3x5-16 | | 10-x/4x | | 6(2x+2)+15= | | -2/-1 | | 0=x^4-6x^3-x^2+20x | | 2.6-5.1=6.6 | | 3x/4-1/3(3x-6)=5/2(6-x/2) | | 6(2x^2-9x-18)=0 | | 8x/3-2x-6 | | 11x^3-x+9=x^3+45x^2+x | | 683+2x=53 | | 18-(2m+5)=4+2m-15 | | 6(4x+15)+13x-12= | | 31/5+x=6 | | a=-2(1.4c)+4c | | 18080-5x=8 | | -x-6y=-5 | | 21/5+x=6 | | 4(x-80)+10=-10 | | 4(5x+6)+7(12-x)= | | 3+z=-19 | | -1+a=0.5 |

Equations solver categories